2007
DOI: 10.1093/gerona/62.11.1287
|View full text |Cite
|
Sign up to set email alerts
|

Good News for Elderly Persons: Olfactory Pleasure Increases at Later Stages of the Life Span

Abstract: Understanding of delirium pathogenesis remains limited despite improved diagnosis, and elucidation of risk factors and prognosis. Major advances in neuroimaging offer the possibility of probing the mechanisms and networks involved in delirium and hence improving understanding of this often devastating syndrome. This review describes the current literature of imaging studies in delirium and related conditions, introduces some of the newer capabilities of neuroimaging with magnetic resonance imaging, positron em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…This finding was replicated in two successive experiments and could not be explained by perceived intensity effects. Past studies have shown diverging results regarding this topic [17], [18], [19], [22], and our study using a large number of odorants in the same intensity range offers new insights into this non-consensual issue highlighting for the first time a modulation in odor hedonic valence specifically for pleasant odors in old adults.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This finding was replicated in two successive experiments and could not be explained by perceived intensity effects. Past studies have shown diverging results regarding this topic [17], [18], [19], [22], and our study using a large number of odorants in the same intensity range offers new insights into this non-consensual issue highlighting for the first time a modulation in odor hedonic valence specifically for pleasant odors in old adults.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, studies of the emotional perception of odors during aging are rare and not consensual: in one study, the smells of lavender and spearmint [17] were judged more pleasant by the older subjects, while another study [18] found such an age effect for certain smells (turpentine, garlic and fish became less unpleasant with age and cloves and rose more pleasant) but not for others (orange, leather, cinnamon, spearmint, banana, lemon, anise, coffee, apple, pineapple, licorice). In contrast, by taking into account the hedonic valence of the odor, another study suggested that older subjects exhibit decreased identification abilities of pleasant but not unpleasant odors [19].…”
Section: Introductionmentioning
confidence: 99%
“…Pelletier (2007) reports that there is decreased chemosensation in older people and that it may be a primary influence to explain poor compliance to diets and emphasises the great need for further research in orophyaryngeal dysphagia rehabilitation. Though Markovic et al. (2007) studied smell intensity and hedonics (pleasant or unpleasant sensations) in patients with increasing age.…”
Section: Resultsmentioning
confidence: 99%
“…The three anchor stimuli 1) orange, 2) liquorice, and 3) fish were chosen based on the results of prior studies in the database HeDoS-F (Markovic et al 2007;Thuerauf et al 2008), comprising olfactory data of more than 200 healthy subjects assessed in a nonanchor-measuring condition. Accordingly, the odor orange had received highest pleasantness ratings, fish lowest pleasantness ratings, and liquorice neutral ratings.…”
Section: Olfactory Testingmentioning
confidence: 99%
“…VAS are widely used in a broad range of scientific contexts (Arruda et al 1996;Di Benedetto et al 2005;Wibbenmeyer et al 2011) and have proven high validity and reliability (de Boer et al 2004;Di Benedetto et al 2005;Fähndrich and Linden 1982;Luria 1975). VAS are a common technique for the assessment of olfactory hedonic judgments (Hummel et al 1998;Leon et al 2007;Markovic et al 2007;Royet et al 2001;Thuerauf et al 1999;Thuerauf et al 2000).…”
Section: Introductionmentioning
confidence: 99%